Role of the Regional Representatives Council on Bicameral Parliament System - Alkadri, Riska (Faculty of Law, Universitas Negeri Semarang, 2016)
After third amendment of the Constitution of 1945 (UUD 1945), the Regional Representatives Council (DPD) has been formulated. The amendment directly changed the parliamentary system in Indonesia, from unicameral into bicameral. The authorities of DPD in bicameral system still not clear enough. Although it is stipulated on Article 22D of UUD 1945, the authorities is still limited if compared with House of Representatives (DPR). This paper would discuss and examine the role of regional representative council as a second chamber from representative board in Indonesian. The paper would distinguish beside the authorities also the mechanism applied by DPD and DPR.